The Importance of The Dentist – Patient Relationship in Oral Cancer Treatment - Indrayadi Gunardi; Rahmi Amtha (Scientific Dental Journal, 2017)
Background: There are many instances in oral cancer cases in which a lack of patient cooperation was found to be a hampering factor in the overall case management. A good relationship between dentists and patients should therefore be built in conjunction with other treatment modalities. Case Report: Three complete oral cancer cases with dentist–patient relationship problems are presented. One of the common basic ways to build a good relationship is through communication and empathy. A relationship is also influenced by psychological distress, experience from previous treatments, socioeconomic factors, the healthcare system, time constraints, and belief. Conclusion: No single intervention strategy can improve the compliance of an oral cancer patient. An assessment of patient knowledge and understanding of the regimen along with clear and effective communication and trust in the therapeutic relationship are important in the overall patient management.